Toward Improving Robustness and Accuracy in Unsupervised Domain Adaptation - Soni A.; Dutta T. (My University, 2025)
Adversarial robustness in the context of Unsupervised Domain Adaptation (UDA) is particularly challenging due to the lack of labels in the target domain. Pseudo labels are often used to make adversarial robust models but compromise robustness and accuracy, falling short of the performance due to noise and inaccuracies in these pseudo labels. The main challenges in achieving robustness and accuracy include ensuring reliable pseudo labels and developing effective training methods that bring alignment between clean and adversarial examples of target data. To address these challenges, we propose a novel training method within the self-training paradigm Consistent Attention Mapping with Self Pseudo Label Refinement (CAM+SPLR). It begins with the pre-training of the UDA model, resulting in a UDA pre-trained model, which is initialized into two separate models: the Anchor model and the TargetNet model. The Anchor model encourages the attention maps of clean images and their adversarial counterparts to be similar, while the TargetNet model simultaneously performs self-training using Adversarial target data and refining the pseudo labels. CAM+SPLR improves both semantically relevant key features and pseudo-labels through a two-step stochastic gradient descent process during training. We conducted extensive experiments on benchmark datasets, including OfficeHome, PACS, and VisDA, demonstrating significant improvements in both robustness and accuracy. Our method achieves an average accuracy improvement of 6% and 8.1% and an average robustness improvement of 10.2% and 4.9%, compared to state-of-the-art methods on the PACS and VisDA datasets. Copyright © 2025, Association for the Advancement of Artificial Intelligence (www.aaai.org). All rights reserved.